2009
DOI: 10.1016/j.cgh.2008.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in the Elderly: Epidemiology, Natural History, and Treatment

Abstract: Hepatitis C continues to be a major public health problem affecting approximately 3% of the global population (1). According to the World Health Organization, an estimated 170 million people have chronic hepatitis C (1). Ten to 20% of those who are chronically infected with chronic hepatitis C will progress to cirrhosis and 5% will develop hepatocellular carcinoma (1). Although the safety and efficacy of hepatitis C therapies have been extensively studied in patients between ages of 18 and 65, patients who are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
4
15
0
2
Order By: Relevance
“…Chronic HCV infection results in the progression to liver cirrhosis and the development of hepatocellular carcinoma. The incidence of hepatocellular carcinoma in cirrhotic patients with chronic HCV infection is approximately 5% per year (2).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic HCV infection results in the progression to liver cirrhosis and the development of hepatocellular carcinoma. The incidence of hepatocellular carcinoma in cirrhotic patients with chronic HCV infection is approximately 5% per year (2).…”
Section: Introductionmentioning
confidence: 99%
“…Weliswaar is de SVR in deze populatie beter met combinatie-dan met monotherapie (met interferon -alfa). 30 Frequente nevenwerkingen( > 30 à 50 %) van interferon-alfa en ribavirine zijn respectievelijk vermoeidheid, koorts, artralgieën, hoofdpijn en respectievelijk hemolyse, dyspepsie en anemie.…”
Section: Hepatitis Bunclassified
“…However Sayed et al [9] reported that the highest prevalence rates in Egypt were seen in patients between 55-65 years old. The age at the time of infection was significantly associated with the development of cirrhosis [7]. The median time from the age of infection to the onset of cirrhosis that was 33 years in patients who acquired the HCV infection at the age of 21 to 30 was reported to decrease to 16 years in patients who had the infection after the age of 40 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the decrease in the incidence of acute hepatitis C, the prevalence of longstanding chronic hepatitis C infection is increasing among older adults [6]. Prevalence of HCV infection in elderly patients are variable allover the world, in a study that was done in Italy among 496 elderly with a mean age of 79.31 years old, the prevalence of positive HCV antibody was found to be around 11% [7]. A study from Japan revealed 8.8% and 13.1% of HCV antibody seropositivity in hospital and autopsy cases older than 60 years of age, respectively [8].…”
Section: Introductionmentioning
confidence: 99%